2018
DOI: 10.3389/fphys.2018.01579
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Dietary Carbohydrates of Intermediary Metabolism in Liver and Muscle of Two Isogenic Lines of Rainbow Trout

Abstract: Rainbow trout (Oncorhynchus mykiss) is recognized as a typical “glucose-intolerant” fish, and the limits of dietary carbohydrate utilization have been investigated for many years. In this study, the objective was to test the molecular effects of dietary carbohydrates on intermediary metabolism in two major metabolic tissues, liver and muscle. Another objective was also to study if the response to carbohydrate intake depended on the genetic background. We fed two isogenic lines of rainbow trout (named A22h and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
6
20
1
Order By: Relevance
“…The mRNA levels of genes involved in β‐oxidation ( cpt1a ) and lipolysis ( lpl ) in the liver of fish were not affected or down‐regulated with the increase in carbohydrate levels in some studies (Cai et al, ; Castro et al, ). In this study, the induced lipolysis in Japanese flounder fed the enriched carbohydrates diet (C200) was unexpected, supporting by the increase in hsl2 mRNA levels and activities of TLP and CPT1, like previous studies in rainbow trout and gilthead sea bream (Bou et al, ; Song, Marandel, Skiba‐Cassy, et al, ). Interestingly enough, another previous study reported that, like in mammalian adipose tissue, glucose enhances lipolysis in rainbow trout hepatocytes incubated in vitro (Harmon & Sheridan, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mRNA levels of genes involved in β‐oxidation ( cpt1a ) and lipolysis ( lpl ) in the liver of fish were not affected or down‐regulated with the increase in carbohydrate levels in some studies (Cai et al, ; Castro et al, ). In this study, the induced lipolysis in Japanese flounder fed the enriched carbohydrates diet (C200) was unexpected, supporting by the increase in hsl2 mRNA levels and activities of TLP and CPT1, like previous studies in rainbow trout and gilthead sea bream (Bou et al, ; Song, Marandel, Skiba‐Cassy, et al, ). Interestingly enough, another previous study reported that, like in mammalian adipose tissue, glucose enhances lipolysis in rainbow trout hepatocytes incubated in vitro (Harmon & Sheridan, ).…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with previously reported studies in silver sea bream (Sparus sarba), rainbow trout (Oncorhynchus mykiss) and Wuchang bream (Megalobrama amblycephala) (Leung & Woo, 2012;Zhou et al, 2013). In the present study, intake of 120 g/kg dietary carbohydrates induced higher hepatic mRNA levels of gck and pfkl and HK activity, which are the rate-limiting genes in glycolysis (Massa, Gagliardino, & Francini, 2011;Song, Marandel, Skiba-Cassy, et al, 2018). Besides, the rate of gluconeogenesis is principally controlled by certain unidirectional enzymes, such as PEPCK and G6Pase (Enes et al, 2009).…”
Section: Response To Increased Dietary Carbohydratesglucose Metabolismsupporting
confidence: 94%
“…There is however margin for improvement and revision of these metabolic models, particularly in the context of aquaculture, as incredibly versatile trait-selected fish (e.g. Fat and Lean lines of rainbow trout) unveiled the combined effects of i) modulation of lipogenesis in the liver by the mTOR pathway (Skiba-Cassy et al, 2009), ii) modulation of muscle glycolytic (PK and PFK) (Song et al, 2018) and fatty acid oxidation enzymes (CPT1, HOAD and ACO) (Jin et al, 2014a), and finally iii) improved response to insulin (Jin et al, 2014b) to achieve fish able to display higher muscle lipid content.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, while the aquaculture industry seeks to further stretch the optimization of fish feed production, the administration of isotopes will provide deeper insights into the regulation of lipid storage and oxidation in fish species in response to different combination of macronutrients. This may be particularly interesting in the procurement of new species to farm or in the optimization and selection of existing ones, currently happening by trait preference (Jin et al, 2014b;Song et al, 2018) or by recurring to the wide spectrum of metabolic responses occurring in nature (Betancor et al, 2016;Marandel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong interaction between glucose and fatty acids in fish, and this affects glucose and lipid utilization (Menoyo et al, 2006;Song et al, 2018). Dietary lipids can be converted to glucose through gluconeogenesis, and alternatively, glucose can be deposited as lipids in fish tissue (Honorato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%